Human Capital Depreciation - Michael Dinerstein; Rigissa Megalokonomou; Constantine Yannelis (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Human capital can depreciate if skills are unused. But estimating human capital depreciation is challenging, as worker skills are difficult to measure and less productive workers are more likely to spend time in non-employment. We overcome these challenges with new administrative data on teachers assignments and their students outcomes, and quasi-random variation from the teacher assignment process in Greece. We find significant losses to output, as a one-year increase in time without formal employment lowers students test scores by 0.09 standard deviations. Using a simple production model, we estimate a skill depreciation rate of 4.3% and experience returns of 6.8%.
Keywords: J01; J24; I29; 330; human capital; unemployment; teachers